Credo (a4) - Kyrie Gloria Credo (a5) - Ockeghem, Johannes c. 1410-1497; Benthem, Jaap van (Utrecht Koninklijke vereniging voor Nederlandse muziekgeschiedenis, 1996)
The first work is for 4 voices (suggested: Discantus, Contratenor altus, Tenor, Bassus), unacc.; the second work for 5 voices ([Discantus], Contratenor, Tenor, Tenor [secundus], Bassus), unacc.Latin words.Historical and editorial notes in English.Includes bibliographical references.